Journal of intercultural communication research
The Journal of Intercultural Communication Research ( JICR )is a publication of the World Communication Association. JICR publishes qualitative and quantitative research that focuses on interrelationships between culture and communication. Generally, research published in JICR emphasizes non-mediated contexts.Submitted manuscripts may report results from either cross-cultural comparative research or results from other types of research concerning the ways culture affects human symbolic activities. Studies reporting data from within a single nation/culture should focus on cultural factors and explore the theoretical or practical relevance of their findings from a cross-cultural perspective.